Does the Routine Skin-Only Closure in Ruptured Abdominal Aortic Aneurysm Repair Safely Diminish Abdominal Compartment Syndrome? A Hypothesis Generating Retrospective Study - Kontopodis, Nikolaos; Lasithiotakis, Konstantinos; Tzartzalou, Ifigeneia; Kasiolas, Ioannis; Kafetzakis, Alexandros; Chrysos, Emmanuel; Ioannou, Christos V. (AORTA, 2023)
Background Abdominal compartment syndrome (ACS) often complicates ruptured abdominal aortic aneurysm (rAAA) repair. We report results with routine skin-only abdominal wound closure after rAAA surgical repair.Methods This was a single-center retrospective study including consecutive patients undergoing rAAA surgical repair for the duration of 7 years. Skin-only closure was routinely performed, and if possible, secondary abdominal closure was performed during the same admission. Demographic information, preoperative hemodynamic condition, and perioperative information (ACS, mortality, rate of abdominal closure, and postoperative outcomes) were collected.Results During the study period, 93 rAAAs were recorded. Ten patients were too frail to undergo repair or refused treatment. Eighty-three patients underwent immediate surgical repair. The mean age was 72.4 ± 10.5 years, and the vast majority were male (82:1). Preoperative systolic blood pressure <90 mm Hg was recorded in 31 patients. Intraoperative mortality was recorded in nine cases. Overall in-hospital mortality was 34.9% (29/83). Primary fascial closure was performed in five patients, while skin-only closure was performed in 69. ACS was recorded in two cases in whom skin sutures were removed and negative pressure wound treatment was applied. Secondary fascial closure was feasible in 30 patients during the same admission. Among 37 patients not undergoing fascial closure, 18 died and 19 survived and were discharged with a planned ventral hernia repair. Median length of intensive care unit and hospital stay were 5 (1–24) and 13 (8–35) days, respectively. After a mean follow-up of 21 months, telephone contact was possible with 14/19 patients who left the hospital with an abdominal hernia. Three reported hernia-related complications mandating surgical repair, while in 11, this was well tolerated.Conclusion Routine skin-only closure during rAAA surgical repair results in low rates of ACS at the expense of a high rate of patients being discharged with a planned ventral hernia which, however, seems to be well tolerated by the majority of patients.
Keywords: ruptured abdominal aortic aneurysm; abdominal compartment syndrome; intra-abdominal pressure; open abdomen